2019
DOI: 10.1186/s13756-019-0520-8
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of Pseudomonas aeruginosa bloodstream infections: prevalence, risk factors, and outcome in carbapenem-susceptible and -non-susceptible infections

Abstract: Background Pseudomonas aeruginosa (PA) is a leading cause of nosocomial infections, and carbapenem non-susceptible strains are a major threat to patient safety. Methods A single center, retrospective comparative analysis of carbapenem-non-susceptible PA (CnSPA) and carbapenem-susceptible PA (CSPA) bloodstream infections (BSIs) was conducted between January 1, 2007, and December 31, 2016. Prevalence and risk factors associated with CnSPA BSIs were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 36 publications
(35 reference statements)
8
34
1
Order By: Relevance
“…As with the previous research, 9 , 16 , 28 , 29 the present study had also demonstrated that the mortality was higher in patients with older ages, serious underlying host diseases (cardiovascular disease, chronic lung disease and diabetes mellitus), the primary site of lung infection and coinfection with other bacteria in univariate analysis. Even so, the results of the multivariate analysis indicated that cardiovascular disease, rather than others above, had 3.978 times the risk of death than those without.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As with the previous research, 9 , 16 , 28 , 29 the present study had also demonstrated that the mortality was higher in patients with older ages, serious underlying host diseases (cardiovascular disease, chronic lung disease and diabetes mellitus), the primary site of lung infection and coinfection with other bacteria in univariate analysis. Even so, the results of the multivariate analysis indicated that cardiovascular disease, rather than others above, had 3.978 times the risk of death than those without.…”
Section: Discussionsupporting
confidence: 89%
“… 37 , 38 Thus, an appropriate choice of effective antibiotics according to the antimicrobial sensitivity test in vitro is critical to improving poor outcomes for patients with P. aeruginosa bacteremia. 29 , 36 Furthermore, the previous studies have reported the existence of the correlation between the virulence genotype and antimicrobial resistance including carbapenems. 10 , 39 As a result, it is also essential to study the associations between virulence and CRPA or MDRPA phenotype to clarify the mechanism for disease severity in patients with drug-resistant phenotypes in future, which will provide the theory of basis for the development of novel antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained data regarding antimicrobial resistance indicate that levels of resistance of P. aeruginosa strains isolated from north-western Poland are comparable with results for the whole country [28]. According to the 2017 ECDC survey, the average resistance rate to carbapenems (imipenem + meropenem) was 24.2% across Poland, whereas in this research, 28.71% of strains were resistant to carbapenems.…”
Section: Bacterial Isolatessupporting
confidence: 76%
“…In other medical units, the transmission of strains between patients was also possible, however, less frequent. The risk of colonisation by P. aeruginosa hospital strains at ICUs is higher presumably due to the prolonged stay of patients, the severity of their illness and exposure to invasive medical procedures [ 28 ]. Detection of strains disseminated in hospital wards seems critically important for immunocompromised patients and other patients susceptible to P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 99%